2018
DOI: 10.3147/jsfp.53.78
|View full text |Cite
|
Sign up to set email alerts
|

<i>Francisella halioticida</i>, Identified as the Most Probable Cause of Adductor Muscle Lesions in Yesso scallops <i>Patinopecten yessoensis</i> Cultured in Southern Hokkaido, Japan

Abstract: The occurrence of orange/pinkish colored lesions in the adductor muscle of Yesso scallops Patinopecten yessoensis has been known for many years in Japan; however, determination of the causative agent has not been adequately investigated. Histological examination of affected scallops in southern Hokkaido typically revealed intense host responses: hemocyte infiltration, an abundance of necrotic hemocytes, lysis of muscle fibers and in some instances melanin deposits when the lesions occurred adjacent to the shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…In a multi-parametric field study to identify potential causes of high mortality of mussels, Charles et al (2020) reported the occurrence of heavy haemocyte infiltra-tion and formation of granulomatous lesions in the connective tissue of various organs, however were not able to identify an aetiological agent. Similarities between the histological observations in mussels and the histopathology reported in Yesso scallops infected with F. halioticida (Meyer et al 2017, Kawahara et al 2018) is what prompted this investigation to test for the presence of F. halioticida in French mussel samples from previous studies.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…In a multi-parametric field study to identify potential causes of high mortality of mussels, Charles et al (2020) reported the occurrence of heavy haemocyte infiltra-tion and formation of granulomatous lesions in the connective tissue of various organs, however were not able to identify an aetiological agent. Similarities between the histological observations in mussels and the histopathology reported in Yesso scallops infected with F. halioticida (Meyer et al 2017, Kawahara et al 2018) is what prompted this investigation to test for the presence of F. halioticida in French mussel samples from previous studies.…”
Section: Introductionsupporting
confidence: 60%
“…The gram-negative bacteria Francisella halioticida was originally described in farmed abalone (Haliotis gigantea) as the cause of mass mortality that occurred in Japan (Kamaishi et al 2010, Brevik et al 2011. Subsequently, this bacterium was identified in diseased Yesso scallops, Mizuhopecten (=Patinopecten) yessoensis, in conjunction with mortality events in Canada (Meyer et al 2017) and Japan (Kawahara et al 2018). In addition, Kawahara et al (2019) demonstrated that this bacterium can be highly virulent in Yesso scallops.…”
Section: Introductionmentioning
confidence: 99%
“…experiencing mortalities in France (Charles et al, 2020). In those reports, F. halioticida occurred mostly intracellularly but without forming microcolonies similar to those typical of IMC; the infection was associated with severe inflammatory reactions, frequently associated with the formation of granuloma-like structures in the infected yesso scallops (Kamaishi et al, 2010;Meyer et al, 2017;Kawahara et al, 2018) and in Mytilus spp. (Charles et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Further taxonomic studies classified F. halioticida strain Shimane-1 as a novel organism, sharing a nucleotide identity of ∼98% of the 16S rRNA gene with isolates of F. philomiragia and F. noatunensis (Brevik et al, 2011). Later on, F. halioticida was recorded causing mortality in yesso scallops in Canada (Meyer et al, 2017) and Japan (Kawahara et al, 2018(Kawahara et al, , 2019, and more recently reported in mussels Mytilus spp. experiencing mortalities in France (Charles et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Francisella is pleomorphic intracellular bacteria, which can cause zoonotic tularemia in humans and many animal species (Pechous et al 2009). It was observed to dominate in the adductor muscle lesions of Yesso scallop, and considered to be the probable causative agent of the lesions (Kawahara et al 2018; Meyer et al 2017). Photobacterium was also considered as a bacterial pathogen for many marine animals including fishes, molluscs, crustaceans, and corals (Moi et al 2017; Thompson et al 2005).…”
Section: Discussionmentioning
confidence: 99%